Circuits Regulating Pleasure and Happiness—Mechanisms of Depression - Loonen, Anton J. M.; Ivanova, Svetlana A. (Frontiers in Human Neuroscience, 2016)
According to our model of the regulation of appetitive-searching vs. distress-avoiding behaviors, the motivation to display these essential conducts is regulated by two parallel cortico-striato-thalamo-cortical, re-entry circuits, including the core and the shell parts of the nucleus accumbens, respectively. An entire series of basal ganglia, running from the caudate nucleus on one side, to the centromedial amygdala on the other side, controls the intensity of these reward-seeking and misery-fleeing behaviors by stimulating the activity of the (pre)frontal and limbic cortices. Hyperactive motivation to display behavior that potentially results in reward induces feelings of hankering (relief leads to pleasure). Hyperactive motivation to exhibit behavior related to avoidance of misery results in dysphoria (relief leads to happiness). These two systems collaborate in a reciprocal fashion. In clinical depression, a mismatch exists between the activities of these two circuits: the balance is shifted to the misery-avoiding side. Five theories have been developed to explain the mechanism of depressive mood disorders, including the monoamine, biorhythm, neuro-endocrine, neuro-immune, and kindling/neuroplasticity theories. This paper describes these theories in relationship to the model (described above) of the regulation of reward-seeking vs. misery-avoiding behaviors. Chronic stress that leads to structural changes may induce the mismatch between the two systems. This mismatch leads to lack of pleasure, low energy, and indecisiveness, on one hand, and dysphoria, continuous worrying, and negative expectations on the other hand. The neuroplastic effects of monoamines, cortisol, and cytokines may mediate the induction of these structural alterations. Long-term exposure to stressful situations (particularly experienced during childhood) may lead to increased susceptibility for developing this condition. This hypothesis opens up the possibility of treating depression with psychotherapy. Genetic and other biological factors (toxic, infectious, or traumatic) may increase sensitivity to the induction of relevant neuroplastic changes. Reversal or compensation of these neuroplastic adjustments may explain the effects of biological therapies in treating depression.